2019
DOI: 10.1086/703376
|View full text |Cite
|
Sign up to set email alerts
|

The Precarious State of Subsistence: Reevaluating Dental Pathological Lesions Associated with Agricultural and Hunter-Gatherer Lifeways

Abstract: Numerous bioarchaeological studies emphasize an increase in dental lesions associated with the transition to agricultural subsistence. Over the years, this diachronic trend has led to the conflation and oversimplification of specific dental indicators of oral health with broad subsistence strategies, emphasizing intergroup variation at the expense of intragroup variation. In order to explore such hidden variation, this metastudy uses published data from 185 archaeological sites to test the hypothesis that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 134 publications
0
11
0
Order By: Relevance
“…Gum diseases became more common as barley and wheat consumption increased [44]. Tooth decay also became more common as wheat and sugar consumption increased [45]. Crooked teeth may be caused by today's widespread consumption of soft foods.…”
Section: Changes In Dietmentioning
confidence: 99%
“…Gum diseases became more common as barley and wheat consumption increased [44]. Tooth decay also became more common as wheat and sugar consumption increased [45]. Crooked teeth may be caused by today's widespread consumption of soft foods.…”
Section: Changes In Dietmentioning
confidence: 99%
“…Tayles et al find the relationship inapplicable to Southeast Asian rice‐based populations (Tayles et al, 2000). One recent study suggested significant differences in average caries prevalence between agricultural and hunter‐gatherer populations alongside a high overlap (>70%) between different subsistence strategies, whereby only 13.6% of variation can be explained by subsistence strategy (Marklein et al, 2019). Given the difficulties of deducing subsistence strategies from dental caries, evidence from multiple disciplines is required to strengthen any claims to the former relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Their simultaneous study has been conducted on the grounds that cariogenic food (mostly of carbohydrate content) promotes caries, leading to periapical cavities, tooth loss, and periodontitis. In that context, dietary shifts from the protein based consumption patterns of foragers to the consumption of carbohydrates or processed food due to the advent of agriculture have been widely studied in past populations showing an increasing trend in the frequency of periodontitis among agriculturalists compared to hunter-gatherers (e.g., Beckett and Lovell, 1994;Frayer, 1984;Klaus and Tam, 2010;Larsen, 1995;Marklein et al, 2019;Munoz, 2017;Sakashita et al, 1997;Scott et al, 1992). The differential access to certain foodstuffs based on sex has been also the focus of bioarchaeological studies, revealing no uniform trends, with some studies showing a higher frequency of periodontitis among men (in agreement with clinical research, see above) (e.g., DeWitte, 2012;Šlaus, 2000;Tomczyk et al, 2018;Wasterlain et al, 2011), others among females (e.g., Tuggle and Watson, 2019;Watson et al, 2010), and others no differences between sexes (e.g., Giuffra et al, 2020).…”
Section: Periodontitismentioning
confidence: 99%
“…Several studies have been conducted in the field of physical anthropology and bioarchaeology, including periapical cavities among the examined variables, attributing them among others to nutritional deficiencies and caries (Giuffra et al, 2020;Figure 5.6: Female young adult left mandibular ramus showing the presence of a periapical cavity (arrow) with associated gross caries (circle); Tomb 15 -skeleton a of the Pontokomi-Vrysi skeletal assemblage, Kozani, Greece, 1 st to 4 th century CE (photo by Vergidou C. with the kind permission of Dr. Karamitrou-Mentessidi). Keenleyside, 2008;Lukacs, 1992;Marklein et al, 2019;Pētersone-Gordina and Gerhards, 2011;Šlaus et al, 2010;. Periapical lesions can be identified on dry bones in the form of focal cavities of various size located at the alveolar bone surrounding the infected tooth.…”
Section: Periapical Cavitiesmentioning
confidence: 99%
See 1 more Smart Citation